Hydrazine Electrooxidation Mediated by Transition Metal Octaethylporphyrin-Modified Electrodes - Arce-Escobar, R; Arce-Escobar, R (Royal Society of Chemistry, 2016)
This work presents the generation of new systems composed of glassy carbon electrodes (GC) modified with commercially available transition metal octaethylporphyrins, M-OEP (M = CoII, CuII, ZnII, RuII, FeIII, NiII) for the electrooxidation of hydrazine at neutral pH. It was found that the most active system corresponds to GC electrodes modified with CoII-OEP adsorbed on the surface, evidencing the importance of the central metal. This system, whose preparation is quick and easy, has been reported to have great electrocatalytic activity on systems and unmodified GC electrodes, which has been corroborated by using electrochemical impedance spectroscopy techniques. In addition, this system provides a very good linear response to the analyte concentration, as well as high accuracy and exactitude. Thus, limits of detection and quantification of 0.0518 and 0.173 mmol L-1, respectively, were determined. These good characteristics envisage the possibility of developing a sensitive amperometric sensor. Furthermore, SEM, AFM and Raman studies revealed the actual modification produced on the electrode surface. © The Royal Society of Chemistry and the Centre National de la Recherche Scientifique 2016.